The Influence and Continuance Intention of the E-Government System: A Case Study of Community Water Supply Business - Sukma, Narongsak; Leelasantitham, Adisorn (Frontiers in Environmental Science, 2022)
The e-Service system is utilized in government administration to help achieve efficiency and provide people with services that meet their needs. This service is also known as e-Government. This article discovers the actual impacts and examines the paper to identify the underlying factors affecting the government's e-service system. The Administration created it to help achieve efficiency and provide people with services that meet their needs, also known as e-government. In addition, it leads to an increase in participation in the equity of the distribution of social benefits. This research examines the essential aspects that influence a community's perception of E-Government Continuance Intentions Toward E-Services. A questionnaire with a five-point Likert scale was issued to 1,000 community water consumers, and the researcher received 627 valid responses. Data were collected using a simple random sampling technique with a sampling ratio of 14 villages. Subsequently, descriptive statistics characterize the data (frequency distributions, percentages, averages, medians, and standard deviation). Furthermore, PLS-SEM was utilized to study the interactions between variables and launch the conceptual model via partial least squares (PLS) path modeling. This research demonstrates that digital technologies are critical to boosting community expectations and satisfaction with e-Services. Numerous factors contribute to its growth. Moreover, this paper presents an excellent case study approach based on expectation confirmation theory for examining people's community participation behaviors regarding e-services. In addition, community water consumers participate in electronic services by confirming their expectations with satisfaction.